Nanomaterial Safety in the Workplace Pilot Project for Assessing the Impact of the NIOSH Nanotechnology Research Center - Landree, Eric (RAND Corporation, 2015)
RAND researchers use literature reviews and stakeholder interviews to develop a preliminary logic model to help the National Institute for Occupational Safety and Health's Nanotechnology Research Center assess its contributions to improving the safety and health of workers who could be affected by the production, use, reuse, or disposal of engineered nanomaterials.